2016
DOI: 10.5152/balkanmedj.2016.16699
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health, Obesity Status and Nutritional Habits in Turkish Children and Adolescents: An Epidemiological Study

Abstract: Background: Studies evaluating the relationship between oral health status and obesity have provided conflicting data. Therefore, there is a great need to investigate and clarify the possible connection in a comprehensive sample. Aims: To assess the relationship of obesity and oral health status among children and adolescents aged 6 to 17 yearsold. Study Design: Cross-sectional study. Methods: Data were obtained from 4,534 children and adolescents (2,018 boys and 2,516 girls). Questionnaires were sent home pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
2
19
0
3
Order By: Relevance
“…Obesity and periodontitis are serious public health problems. Several authors have reported the association between obesity or overweight and periodontal disease in children, adolescents and adults . Some of the mechanisms reported in the literature between the association of overweight or obesity and periodontal disease are as follows: (i) Poor dietary patterns, such as low calcium and vitamin C intake and higher intakes of sugars and fat, may affect oral tissues and immune response .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Obesity and periodontitis are serious public health problems. Several authors have reported the association between obesity or overweight and periodontal disease in children, adolescents and adults . Some of the mechanisms reported in the literature between the association of overweight or obesity and periodontal disease are as follows: (i) Poor dietary patterns, such as low calcium and vitamin C intake and higher intakes of sugars and fat, may affect oral tissues and immune response .…”
Section: Discussionmentioning
confidence: 99%
“…Being overweight, obesity and periodontal disease represent a serious public health problem in children and adults . Obesity and overweight are defined by the World Health Organization as diseases in which body fat or adipose tissue is accumulated abnormally or excessively, affecting the general health . The body mass index (BMI) is a value derived from the weight and height of an individual.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, the results want to focus the attention on the negative impact of obesity on gingival health in young subjects, probably due to a combination of factors, like metabolic and inflammatory profiles and the result of a careless attitude towards prevention diseases of the oral cavity, including hygiene procedures at home, knowledge of a balance diet and respect for periodic check-up to the dentist (29,30). In the literature is described the possibility of using protective microorganisms present in dental plaque as Lactobacillus brevis to suppress the growth of pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%